Effect of Human Mesenchymal Stem Cells on Xenogeneic T and B Cells Isolated from Lupus-Prone MRL.Faslpr Mice - Hong Kyung Lee; Eun Young Kim; Hyung Sook Kim; Eun Jae Park; Hye Jin Lee; Tae Yong Lee; Kyung Suk Kim; Sang-Cheol Bae; Jin Tae Hong; Youngsoo Kim; Sang-Bae Han (Hindawi Limited, 2020)
Systemic lupus erythematosus (SLE) is an autoimmune disease, which is characterized by hyperactivation of T and B cells. Human mesenchymal stem cells (hMSCs) ameliorate the progression of SLE in preclinical studies using lupus-prone MRL.Faslpr mice. However, whether hMSCs inhibit the functions of xenogeneic mouse T and B cells is not clear. To address this issue, we examined the in vitro effects of hMSCs on T and B cells isolated from MRL.Faslpr mice. Naïve hMSCs inhibited the functions of T cells but not B cells. hMSCs preconditioned with IFN-γ (i) inhibited the proliferation of and IgM production by B cells, (ii) attracted B cells for cell-cell interactions in a CXCL10-dependent manner, and (iii) inhibited B cells by producing indoleamine 2,3-dioxygenase. In summary, our data demonstrate that hMSCs exert therapeutic activity in mice in three steps: first, naïve hMSCs inhibit the functions of T cells, hMSCs are then activated by IFN-γ, and finally, they inhibit B cells.